Decriminalization and medical students attitudes to same sex behaviour. (19th May 2022) - Kar, Anindya; Arneaud, Gervan J.; Majumder, Sunrit; Bhugra, Dinesh; Pal, Anasua
Abstract: The Supreme Court of India, decriminalized same-sex activities in 2018 but the Indian medical curriculum has not been updated and inclusive of the sexual minorities despite the change. This study explores the attitude of medical students towards same-gender attraction and how it has shaped and reshaped in an ever-changing social environment. Medical students of four reputed Indian medical colleges were asked to self-administer an 18-item questionnaire anonymously. Internal consistency of the questionnaire statements was high. Of 729 initial responses, 84 were omitted for giving incomplete responses and 3 were omitted for not being Indian. A total of 642 responses was included in the analysis. More than 80% of the students believed homosexuality is a sexual orientation whereas only 15% believed it is an acquired behaviour and only 1.9% considered it an illness. However, more than 95%of students agreed that homosexuality is not an illness. Although the overall attitude of Indian medical students has changed since decriminalization, urgent work on the medical curriculum is needed to change some negative attitudes so that patients receive appropriate care.